ANALYSIS OF TRAINING PROGRAMS OF SCHOOL TEACHERS IN ROMANIA IN 2021 - Gabriela MOTOI; Alexandrina Mihaela POPESCU (Universitaria Publishing House, Craiova, 2022)
The pandemic has brought educational systems in front of certain changes in the educational paradigm and at the same time in front of enormous challenges. Online education has been a reality for many months, and teachers have worked hard to adapt to the situation created by the crisis facing schools. It was a period that very often brought to the surface the creativity of teachers and the great availability to adapt to the situation of online education. Depending on the environment of residence, the infrastructure of the schools, the digital competencies they possessed, the teachers found solutions so as not to further increase the inequalities between the students. We proposed making a synthetic analysis of the training programs of school teachers in Romania, having 2021 as reference year, a pandemic year. This analysis was carried out at the level of development regions, at the level of the structure of the providers of continuous training programs and of the topics of continuous training.